Treatment Success in Trypanosoma cruzi Infection Is Predicted by Early Changes in Serially Monitored Parasite-Specific T and B Cell Responses - Alvarez, María G (2016)
Fil: Alvarez, María G. Hospital Interzonal General de Agudos Eva Perón, Buenos Aires; Argentina.